Quick-charge type lithium ion battery and preparation method thereof
By optimizing the composition and proportion of the positive and negative electrode materials of lithium iron phosphate batteries, the combination surface density, compaction control and the optimization of electrolyte formula, the problems of capacity attenuation and low energy density of traditional lithium iron phosphate batteries in the fast charging cycle are solved. A fast charging lithium-ion battery with high energy density and long cycle life is achieved.
Patent Information
- Application Number
- CN202411606933.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-07
AI Technical Summary
Traditional lithium iron phosphate batteries have rapid capacity decays during the fast charging cycle and have low energy density, which cannot meet the needs of long-range battery life, fast charging and long-life warranty.
By optimizing the composition and proportion of the positive and negative electrode materials, including the use of materials such as lithium iron phosphate, conductive carbon black, multi-wall carbon nanotubes and polyvinylidene fluoride, combined with appropriate surface density and compaction control, the electrolyte formulation is optimized to ensure that Lithium ions diffuse rapidly and circulate stably.
The energy density of lithium-ion batteries has been increased to 176Wh/Kg, the battery's normal temperature cycle capacity has reached more than 5,000 weeks, the rate capacity has been increased to more than 2C, and the fast charging cycle life can reach more than 3,000 weeks.
Smart Images

Figure CN119400932A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a fast-charging lithium ion battery and a preparation method thereof. Background Art
[0002] With the development of social economy, the demand for new and efficient energy storage equipment is becoming more and more urgent, and higher requirements are put forward for factors such as energy density, fast charging capability, cycle life, safety and cost. Lithium iron phosphate cells have more advantages in safety performance and cost than ternary cells, and are also accepted by most new energy vehicle users. However, the capacity of traditional lithium iron phosphate batteries decays rapidly during the fast charging cycle, and the energy density is as low as 160-170Wh / Kg, which cannot meet the current customer demand for long-range endurance, fast charging and long life warranty. Therefore, how to improve the energy density and fast charging cycle capacity of lithium iron phosphate batteries while ensuring costs has become one of the major challenges faced by the new energy battery industry. Summary of the invention
[0003] Based on the technical problems existing in the background technology, the present invention proposes a fast-charging lithium-ion battery and a preparation method thereof.
[0004] The invention provides a fast-charge lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte.
[0005] The lithium ion battery provided in the present invention has high energy density and excellent cycle capacity.
[0006] Preferably, the positive electrode sheet comprises a positive electrode current collector and a positive electrode slurry coated on the positive electrode current collector; the positive electrode slurry comprises lithium iron phosphate, conductive carbon black, multi-walled carbon nanotube slurry, and polyvinylidene fluoride.
[0007] More preferably, the mass fraction of the multi-walled carbon nanotubes in the multi-walled carbon nanotube slurry is 3-6wt%.
[0008] More preferably, the diameter of the multi-walled carbon nanotubes in the multi-walled carbon nanotube slurry is 2-100 nm, and the length is 0.1-50 μm.
[0009] More preferably, the mass ratio of the lithium iron phosphate, conductive carbon black, multi-walled carbon nanotube slurry and polyvinylidene fluoride is (97.2-98): (0.3-0.6): (0.15-0.4): (1.5-2.2).
[0010] Controlling the mass ratio of lithium iron phosphate, conductive carbon black, multi-walled carbon nanotube slurry, and polyvinylidene fluoride within a certain range will not only help increase the content of the main materials, but also help improve the conductivity of the positive electrode sheet and reduce impedance.
[0011] More preferably, the positive electrode current collector is a carbon-coated aluminum foil with a thickness of 10-15 μm, and the carbon-coated layer is 0.5-2 μm.
[0012] More preferably, the coating surface density of the positive electrode slurry on the positive electrode sheet is 420-490 g / m 2 .
[0013] More preferably, the positive electrode sheet compaction is controlled at 2.45-2.6 g / cm 3 .
[0014] Preferably, the negative electrode sheet comprises a negative electrode current collector and a negative electrode slurry coated on the negative electrode current collector; the negative electrode slurry components include carbon-coated artificial graphite, conductive carbon black, single-walled carbon nanotube slurry, sodium carboxymethyl cellulose, and styrene-butadiene rubber.
[0015] More preferably, the single-walled carbon nanotube slurry is an ultrafine dispersion of single-walled carbon nanotubes in water, wherein the mass fraction of the single-walled carbon nanotubes is 0.1-1 wt %.
[0016] More preferably, the diameter of the single-walled carbon nanotubes in the single-walled carbon nanotube slurry is 0.5-10 nm, and the length is 1-50 μm.
[0017] More preferably, the mass ratio of the carbon-coated artificial graphite, conductive carbon black, single-walled carbon nanotube slurry, sodium carboxymethyl cellulose and styrene-butadiene rubber is (96.3-97.5): (0.2-0.6): (0-0.03): (0.5-1.5): (1.0-2.2).
[0018] The mass ratio of carbon-coated artificial graphite, conductive carbon black, single-walled carbon nanotube slurry, sodium carboxymethyl cellulose and styrene-butadiene rubber within a certain range helps to maintain the continuity of the conductive network when the particles expand and shrink during long-term cyclic charge and discharge, thereby ensuring long circulation.
[0019] More preferably, the negative electrode current collector is a copper foil with a thickness of 4-6 μm.
[0020] More preferably, the carbon-coated artificial graphite has a D50 particle size of 12-15 μm, a D10 particle size of 6-8 μm, and a D90 particle size of 24-26 μm.
[0021] The particle size of carbon-coated artificial graphite is within a certain range, which is conducive to the rapid diffusion of lithium ions.
[0022] More preferably, the coating surface density of the negative electrode slurry on the negative electrode sheet is 200-230 g / m 2 .
[0023] Appropriate surface density design improves energy density while ensuring the lithium ion diffusion path and ensuring rapid diffusion capability.
[0024] More preferably, the negative electrode sheet compaction is controlled at 1.5-1.68 g / cm 3 .
[0025] Controlling the compaction of the negative electrode within a certain range helps to increase the effective pores and reduce the tortuosity of the pores, as well as increase the electrode's liquid retention capacity and ensure Li + Rapid diffusion channel.
[0026] Preferably, the electrolyte comprises lithium salt, solvent and additives.
[0027] More preferably, the room temperature conductivity of the electrolyte is above 9 mS / cm.
[0028] More preferably, the lithium salt is selected from at least two of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide and lithium bis(trifluoromethylsulfonyl)imide, and the mass of the lithium salt accounts for 12-16% of the total mass of the electrolyte.
[0029] More preferably, the solvent is selected from one or more of ethylene carbonate, propylene carbonate, methyl ethyl carbonate and dimethyl carbonate, and the mass of the solvent accounts for 68-88% of the total mass of the electrolyte.
[0030] More preferably, the additive is selected from at least five of vinylene carbonate, fluoroethylene carbonate, ethylene sulfate, allyl sulfide, methylene disulfonate, triphosphate, lithium difluorooxalatoborate, and lithium difluorophosphate. The mass of the additive accounts for 2-20% of the total mass of the electrolyte.
[0031] The electrolyte formula ensures high wetting and high conductivity, while forming a thin and stable SEI film on the negative electrode and continuously repairing it, which is conducive to long circulation.
[0032] Preferably, the diaphragm is a 9+2+3 ceramic diaphragm with a thickness of 10-20 μm.
[0033] The present invention also proposes a method for preparing the above-mentioned fast-charging lithium-ion battery, comprising the following steps: winding the positive electrode sheet, the negative electrode sheet, and the separator to make a winding core, and assembling and injecting the electrolyte liquefaction component to obtain a lithium-ion battery.
[0034] The manufacturing method of the present invention is simple and easy to operate, which effectively improves the energy density of the lithium iron phosphate battery and solves the problem of insufficient fast charging cycle capacity.
[0035] The beneficial effects of the present invention are:
[0036] The present invention establishes a scientific match of material components and proportions by means of negative electrode material modification, formula optimization, surface density, compaction optimization and electrolyte optimization, and the energy density of the obtained fast-charge long-cycle lithium-ion battery is increased to 176Wh / Kg, and the battery room temperature cycle capacity reaches more than 5000 weeks, while the rate capacity is increased to more than 2C, and the fast-charge cycle life can reach more than 3000 weeks, effectively improving the problem of insufficient rate capacity and cycle capacity of lithium iron phosphate batteries. The manufacturing method of the present invention is simple and easy, and this fast-charge long-cycle lithium-ion battery meets market demand, has high economic value, and provides product support for the power battery fast-charge market. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a 2.2C / 1C cycle curve of the lithium-ion battery of Example 1 of the present invention at 25°C.
[0038] Figure 2 This is a 1.3C / 1C cycle curve diagram of the lithium-ion battery of Example 1 of the present invention at 25°C.
[0039] Figure 3 This is a 1C / 1C cycle curve diagram of the lithium-ion battery of Example 1 of the present invention at 45°C. DETAILED DESCRIPTION
[0040] The technical solution of the present invention is described in detail through specific embodiments.
[0041] Unless otherwise specified, the materials, reagents, etc. used in the following examples and comparative examples can be obtained from commercial sources.
[0042] Example 1
[0043] A method for preparing a fast-charging lithium-ion battery comprises the following steps: mixing the positive and negative electrodes, coating, rolling, slitting, and laser cutting, winding the positive and negative electrode sheets and separators to form a core, and obtaining a finished battery through conventional battery manufacturing methods such as assembly, baking, primary liquid injection, high-temperature rest, formation, aging, secondary liquid injection, sealing, and capacity division.
[0044] The positive electrode sheet includes a positive electrode current collector and a positive electrode slurry coated on the positive electrode current collector; the positive electrode current collector is a 12μm carbon-coated aluminum foil with a 1μm carbon coating layer; the positive electrode slurry is lithium iron phosphate, conductive carbon black, multi-walled carbon nanotube slurry (mass fraction is 4%), and polyvinylidene fluoride in a mass ratio of 97.4:0.32:0.28:2. The negative electrode sheet includes a negative electrode current collector and a negative electrode slurry coated on the negative electrode current collector; the negative electrode current collector is a 4.5μm copper foil; the negative electrode slurry is carbon-coated artificial graphite (carbon coating ratio 100%), conductive carbon black, single-walled carbon nanotubes (mass fraction is 0.4%), sodium carboxymethyl cellulose, and styrene-butadiene rubber in a mass ratio of 96.5:0.58:0.02:1.1:1.9. The coating surface density of the positive electrode slurry on the positive electrode sheet is 438±3g / m 2 ; The coating surface density of the negative electrode slurry on the negative electrode sheet is 208±3g / m 2 ; The compaction of the positive electrode is controlled at 2.52g / cm 3 The negative electrode sheet compaction is controlled at 1.58g / cm 3 The diaphragm uses a 9+2+3 ceramic coated diaphragm with a thickness of 14μm. The electrolyte includes the following components: the solvent is composed of EC: PC: EMC: DMC in a mass ratio of 30:5:40:25; the lithium salt addition amount is 10% LiPF6, 4% LiFSI; the film-forming additives are 3% VC, 1% FEC, 0.5% DTD, 0.5% AS, and 0.5% LiODFB.
[0045] Example 2
[0046] A method for preparing a fast-charging lithium-ion battery is the same as that in Example 1.
[0047] The positive electrode sheet includes a positive electrode current collector and a positive electrode slurry coated on the positive electrode current collector; the positive electrode current collector is a 12μm carbon-coated aluminum foil with a 1μm carbon coating layer; the positive electrode slurry is lithium iron phosphate, conductive carbon black, multi-walled carbon nanotube slurry (mass fraction is 4%), and polyvinylidene fluoride in a mass ratio of 97.9:0.32:0.18:1.6. The negative electrode sheet includes a negative electrode current collector and a negative electrode slurry coated on the negative electrode current collector; the negative electrode current collector is a 4.5μm copper foil; the negative electrode slurry is carbon-coated artificial graphite (carbon coating ratio 100%), conductive carbon black, single-walled carbon nanotube (mass fraction is 0.4%), sodium carboxymethyl cellulose, styrene-butadiene rubber, and polyacrylic acid in a mass ratio of 97.3:0.38:0.02:0.6:1.0:0.7. The coating surface density of the positive electrode slurry on the positive electrode sheet is 438±3g / m 2 ; The coating surface density of the negative electrode slurry on the negative electrode sheet is 208±3g / m 2 ; The compaction of the positive electrode is controlled at 2.52g / cm 3The negative electrode sheet compaction is controlled at 1.66g / cm 3 The diaphragm uses a 9+2+3 ceramic coated diaphragm with a thickness of 14μm. The electrolyte includes the following components: the solvent is composed of EC: PC: EMC: DMC in a mass ratio of 30:5:40:25; the lithium salt addition amount is 10% LiPF6, 4% LiFSI; the film-forming additives are 3% VC, 1% FEC, 0.5% DTD, 0.5% AS, and 0.5% LiODFB.
[0048] Example 3
[0049] The preparation method of a fast-charging lithium-ion battery is the same as that in Example 1.
[0050] The positive electrode sheet includes a positive electrode current collector and a positive electrode slurry coated on the positive electrode current collector; the positive electrode current collector is a 12μm carbon-coated aluminum foil with a 1μm carbon coating layer; the positive electrode slurry is lithium iron phosphate, conductive carbon black, multi-walled carbon nanotube slurry (mass fraction is 4%), and polyvinylidene fluoride in a mass ratio of 97.4:0.32:0.28:2. The negative electrode sheet includes a negative electrode current collector and a negative electrode slurry coated on the negative electrode current collector; the negative electrode current collector is a 4.5μm copper foil; the negative electrode slurry is carbon-coated artificial graphite (carbon coating ratio 100%), conductive carbon black, single-walled carbon nanotubes (mass fraction is 0.4%), sodium carboxymethyl cellulose, and styrene-butadiene rubber in a mass ratio of 96.4:0.58:0.02:1.1:1.9. The coating surface density of the positive electrode slurry on the positive electrode sheet is 438±3g / m 2 ; The coating surface density of the negative electrode slurry on the negative electrode sheet is 208±3g / m 2 ; The compaction of the positive electrode is controlled at 2.5g / cm 3 The negative electrode sheet compaction is controlled at 1.58g / cm 3 The diaphragm uses a 9+2+3 ceramic coated diaphragm with a thickness of 14μm. The electrolyte includes the following components: the solvent is composed of EC: PC: EMC: DMC in a mass ratio of 30:5:40:25; the lithium salt addition amount is 10% LiPF6, 4% LiFSI; the film-forming additives are 2.5% VC, 0.5% DTD, 0.5% MMDS, 0.5% TMSP, and 0.5% LiPO2F2.
[0051] Example 4
[0052] A method for preparing a fast-charging lithium-ion battery is the same as that in Example 1.
[0053] The positive electrode sheet includes a positive electrode current collector and a positive electrode slurry coated on the positive electrode current collector; the positive electrode current collector is a 12μm carbon-coated aluminum foil with a 1μm carbon coating layer; the positive electrode slurry is lithium iron phosphate, conductive carbon black, multi-walled carbon nanotube slurry (mass fraction is 4%), and polyvinylidene fluoride in a mass ratio of 97.4:0.32:0.28:2. The negative electrode sheet includes a negative electrode current collector and a negative electrode slurry coated on the negative electrode current collector; the negative electrode current collector is a 4.5μm copper foil; the negative electrode slurry is carbon-coated artificial graphite (carbon coating ratio 45%), conductive carbon black, single-walled carbon nanotubes (mass fraction is 0.4%), sodium carboxymethyl cellulose, and styrene-butadiene rubber in a mass ratio of 96.4:0.58:0.02:1.1:1.9. The coating surface density of the positive electrode slurry on the positive electrode sheet is 436±3g / m 2 ; The coating surface density of the negative electrode slurry on the negative electrode sheet is 208±3g / m 2 ; The compaction of the positive electrode is controlled at 2.52g / cm 3 The negative electrode sheet compaction is controlled at 1.58g / cm 3 The diaphragm uses a 9+2+3 ceramic coated diaphragm with a thickness of 14μm. The electrolyte includes the following components: the solvent is composed of EC: PC: EMC: DMC in a mass ratio of 30:5:40:25; the lithium salt addition amount is 10% LiPF6, 4% LiFSI; the film-forming additives are 3% VC, 1% FEC, 0.5% DTD, 0.5% AS, and 0.5% LiODFB.
[0054] Example 5
[0055] A method for preparing a fast-charging lithium-ion battery is the same as that in Example 1.
[0056] The positive electrode sheet includes a positive electrode current collector and a positive electrode slurry coated on the positive electrode current collector; the positive electrode current collector is a 12μm carbon-coated aluminum foil with a 1μm carbon coating layer; the positive electrode slurry is lithium iron phosphate, conductive carbon black, multi-walled carbon nanotube slurry (mass fraction is 4%), and polyvinylidene fluoride in a mass ratio of 97.4:0.32:0.28:2. The negative electrode sheet includes a negative electrode current collector and a negative electrode slurry coated on the negative electrode current collector; the negative electrode current collector is a 4.5μm copper foil; the negative electrode slurry is carbon-coated artificial graphite (carbon coating ratio 100%), conductive carbon black, single-walled carbon nanotubes (mass fraction is 0.4%), sodium carboxymethyl cellulose, and styrene-butadiene rubber in a mass ratio of 96.4:0.58:0.02:1.1:1.9. The coating surface density of the positive electrode slurry on the positive electrode sheet is 482±3g / m 2 ; The coating surface density of the negative electrode slurry on the negative electrode sheet is 226±3g / m 2 ; The compaction of the positive electrode is controlled at 2.57g / cm 3 The negative electrode sheet compaction is controlled at 1.58g / cm3 The diaphragm uses a 9+2+3 ceramic coated diaphragm with a thickness of 14μm. The electrolyte includes the following components: the solvent is composed of EC: PC: EMC: DMC in a mass ratio of 30:5:40:25; the lithium salt addition amount is 10% LiPF6, 4% LiFSI; the film-forming additives are 3% VC, 1% FEC, 0.5% DTD, 0.5% AS, and 0.5% LiODFB.
[0057] Comparative Example 1
[0058] A method for preparing a fast-charging lithium-ion battery is the same as that in Example 1.
[0059] The positive electrode sheet includes a positive electrode current collector and a positive electrode slurry coated on the positive electrode current collector; the positive electrode current collector is a 12μm carbon-coated aluminum foil with a 1μm carbon coating layer; the positive electrode slurry is lithium iron phosphate, conductive carbon black, multi-walled carbon nanotube slurry (mass fraction is 4%), and polyvinylidene fluoride in a mass ratio of 97.4:0.32:0.28:2. The negative electrode sheet includes a negative electrode current collector and a negative electrode slurry coated on the negative electrode current collector; the negative electrode current collector is a 4.5μm copper foil; the negative electrode slurry is carbon-coated artificial graphite (carbon coating ratio 100%), conductive carbon black, single-walled carbon nanotubes (mass fraction is 0.4%), sodium carboxymethyl cellulose, and styrene-butadiene rubber in a mass ratio of 96.5:0.58:0.02:1.1:1.9. The coating surface density of the positive electrode slurry on the positive electrode sheet is 512±3g / m 2 ; The coating surface density of the negative electrode slurry on the negative electrode sheet is 242±3g / m 2 ; The compaction of the positive electrode is controlled at 2.52g / cm 3 The negative electrode sheet compaction is controlled at 1.58g / cm 3 The diaphragm uses a 9+2+3 ceramic coated diaphragm with a thickness of 14μm. The electrolyte includes the following components: the solvent is composed of EC: PC: EMC: DMC in a mass ratio of 30:5:40:25; the lithium salt addition amount is 10% LiPF6, 4% LiFSI; the film-forming additives are 3% VC, 1% FEC, 0.5% DTD, 0.5% AS, and 0.5% LiODFB.
[0060] Comparative Example 2
[0061] A method for preparing a fast-charging lithium-ion battery is the same as that in Example 1.
[0062] The positive electrode sheet includes a positive electrode current collector and a positive electrode slurry coated on the positive electrode current collector; the positive electrode current collector is a 12μm carbon-coated aluminum foil with a 1μm carbon coating layer; the positive electrode slurry is lithium iron phosphate, conductive carbon black, multi-walled carbon nanotube slurry (mass fraction is 4%), and polyvinylidene fluoride in a mass ratio of 97.4:0.32:0.28:2. The negative electrode sheet includes a negative electrode current collector and a negative electrode slurry coated on the negative electrode current collector; the negative electrode current collector is a 4.5μm copper foil; the negative electrode slurry is carbon-coated artificial graphite (carbon coating ratio 100%), conductive carbon black, single-walled carbon nanotubes (mass fraction is 0.4%), sodium carboxymethyl cellulose, and styrene-butadiene rubber in a mass ratio of 96.5:0.58:0.02:1.1:1.9. The coating surface density of the positive electrode slurry on the positive electrode sheet is 438±3g / m 2 ; The coating surface density of the negative electrode slurry on the negative electrode sheet is 208±3g / m 2 ; The compaction of the positive electrode is controlled at 2.52g / cm 3 The negative electrode sheet compaction is controlled at 1.7g / cm 3 The diaphragm uses a 9+2+3 ceramic coated diaphragm with a thickness of 14μm. The electrolyte includes the following components: the solvent is composed of EC: PC: EMC: DMC in a mass ratio of 30:5:40:25; the lithium salt addition amount is 10% LiPF6, 4% LiFSI; the film-forming additives are 3% VC, 1% FEC, 0.5% DTD, 0.5% AS, and 0.5% LiODFB.
[0063] The lithium-ion battery was subjected to a 0.33C / 0.33C constant capacity test at room temperature of 25°C to calculate the energy density, and a 1.3C step charge / 1C and 2.2C / 1C fast charge cycle performance test at room temperature. The test results are shown in Table 1.
[0064] Table 1 Performance data of lithium-ion batteries
[0065]
[0066] It can be seen from the data in Table 1 that Example 1 of the present invention has good fast-charge and long-cycle capabilities. It can be seen from Examples 2 and 5 that the fast-charge cycle capabilities are reduced to varying degrees by increasing the compaction or surface density to increase the energy density of the battery cell. At the same time, it can be seen from Comparative Examples 1 and 2 that the fast-charge cycle capabilities drop rapidly when extreme compaction or ultra-high surface density is used. It can be seen from Example 3 that the combination and content of different electrolyte additives have a great influence on the cycle capacity. It can be seen from Example 4 that the carbon coating ratio decreases and the fast-charge capacity decreases.
[0067] from Figure 1 , Figure 2It can be seen that the lithium-ion battery prepared in Example 1 not only exhibits excellent long cycle capacity in the fast charge cycle, but also Figure 3 It can be seen that lithium-ion batteries also take into account high-temperature cycle capabilities.
[0068] In summary, the lithium ion battery provided by the present invention has excellent rate capability and cycle capacity.
[0069] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A fast-charge lithium-ion battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. The negative electrode sheet comprises a negative electrode current collector and a negative electrode slurry coated on the negative electrode current collector. The mass ratio of carbon-coated artificial graphite, conductive carbon black, single-walled carbon nanotube slurry, sodium carboxymethyl cellulose and styrene-butadiene rubber in the negative electrode slurry is (96.3-97.5): (0.2-0.6): (0-0.03): (0.5-1.5): (1.0-2.2); The mass fraction of the single-walled carbon nanotubes in the single-walled carbon nanotube slurry is 0.1-1wt%; the D50 particle size of the carbon-coated artificial graphite is 12-15μm, the D10 particle size is 6-8μm, and the D90 particle size is 24-26μm; the coating surface density of the negative electrode slurry on the negative electrode sheet is 200-230g / m 2 ; The compaction of the negative electrode sheet is controlled at 1.5-1.68g / cm 3 .
2. The lithium-ion battery according to claim 1, characterized in that The positive electrode sheet includes a positive electrode current collector and a positive electrode slurry coated on the positive electrode current collector, wherein the positive electrode slurry includes lithium iron phosphate, conductive carbon black, multi-walled carbon nanotube slurry, and polyvinylidene fluoride; the coating surface density of the positive electrode slurry on the positive electrode sheet is 420-490 g / m 2 ; The compaction of the positive electrode is controlled at 2.45-2.6g / cm 3 .
3. The lithium-ion battery according to claim 2, characterized in that: The mass ratio of lithium iron phosphate, conductive carbon black, multi-walled carbon nanotube slurry and polyvinylidene fluoride in the positive electrode slurry is (97.2-98): (0.3-0.6): (0.15-0.4): (1.5-2.2); The mass fraction of the multi-walled carbon nanotubes in the multi-walled carbon nanotube slurry is 3-6wt%.
4. The lithium-ion battery according to claim 1, characterized in that: The electrolyte comprises a lithium salt, a solvent and an additive; the lithium salt is selected from at least two of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide and lithium bis(trifluoromethylsulfonyl)imide; the solvent is selected from one or more of ethylene carbonate, propylene carbonate, methyl ethyl carbonate and dimethyl carbonate; the additive is selected from at least five of vinylene carbonate, fluoroethylene carbonate, ethylene sulfate, allyl sulfide, methylene disulfonate, triphosphate, lithium difluorooxalatoborate and lithium difluorophosphate.
5. The lithium-ion battery according to claim 1, characterized in that: The diaphragm is a 9+2+3 ceramic diaphragm with a thickness of 10-20 μm.
6. A method for preparing a lithium ion battery according to any one of claims 1 to 5, characterized in that: The following steps are involved: The positive electrode sheet, the negative electrode sheet and the separator are wound into a core, and then assembled and injected with electrolyte to obtain a lithium-ion battery.
Citation Information
Patent Citations
Lithium ion battery negative electrode sheet containing electric-conduction coating, and preparation method thereof
CN108511685A
Negative plate and preparation method thereof, lithium ion cell, lithium ion battery pack and application of lithium ion battery pack
CN112271271A
Lithium iron phosphate battery capable of improving low-temperature high-rate charge-discharge performance
CN113363557A
Lithium ion battery with excellent low-temperature charge-discharge capacity
CN115360409A
Negative pole piece as well as preparation method and application thereof
CN116581271A
Cited By
Lithium ion battery, battery assembly and electric device
CN121215846A
Lithium ion battery
CN122158664A